THE EFFECT OF USING ONLINE MODULE ON THE LEARNING RESULTS OF UT STUDENTS AT THE FINAL EXAMINATION GRADUATION LEVEL - Kuala Ginting; Gemala Widiyarti (Teunuleh Publisher, 2020)
This research was conducted on students of the UPBJJ UT Medan Open University who focused on the PGSD UT students of the Pandan Tapteng Study group. Based on data analysis and research hypothesis testing carried out in Class A and B semester nine UT students registration period 2020.1 it can be concluded as follows: Student learning outcomes using conventional learning in final semester UT students obtained an average value of 71.43. Student learning outcomes using the online module in the final semester students obtained an average value of 80.24. There is a significant effect of using the online module on UT student learning outcomes at the level of passing the final exam.